1994
DOI: 10.21273/hortsci.29.9.1052
|View full text |Cite
|
Sign up to set email alerts
|

`Redhaven' Peach Impact Damage Thresholds

Abstract: `Redhaven' peaches [Prunus persica (L.) Batsch] were dropped onto several impact surfaces to determine impact conditions that initiate bruising. After impact, the peaches were tested for flesh firmness and sorted into firm, soft, and very soft groups for bruise analysis. The drop height that did not bruise decreased as fruit softened. The peach shoulder area bruised most easily. A drop of only 8 mm onto a hard surface initiated bruising on a soft peach, whereas a Poron 15250 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…A higher firmness or failure stress for stiffer fruits means that they are more resistant to bruising. Several researchers observed increased physical damage with soft peaches (Lin and Brusewitz, 1994;Schulte et al, 1994;Gorny et al, 1998;Metheney et al, 2002). Fruits with higher stiffness will have shorter contact times, which reduce the risk to develop bruises (Van linden et al, 2006a).…”
Section: Effect Of Peach Acoustic Stiffness On Bruise Volumementioning
confidence: 99%
See 2 more Smart Citations
“…A higher firmness or failure stress for stiffer fruits means that they are more resistant to bruising. Several researchers observed increased physical damage with soft peaches (Lin and Brusewitz, 1994;Schulte et al, 1994;Gorny et al, 1998;Metheney et al, 2002). Fruits with higher stiffness will have shorter contact times, which reduce the risk to develop bruises (Van linden et al, 2006a).…”
Section: Effect Of Peach Acoustic Stiffness On Bruise Volumementioning
confidence: 99%
“…Bruise extension is usually described in terms of bruise volume (Blahovec and Paprstein, 2005). Statistical bruise prediction models described in the literature for peach are restricted to the effect of peach ripeness on bruise susceptibility (Hung and Prussia, 1989;Schulte et al, 1991;Vergano et al, 1991;Lin and Brusewitz, 1994;Delwiche et al, 1996;Diezma et al, 2006). The force response of an elastic sphere impacting a rigid surface is governed by the impacting velocity, mass, radius of curvature, elastic modulus, and Poisson ratio of the sphere.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of research has been done related to mechanical damage of agriculture products such as apples [10], peaches [11], tomatoes [12], potatoes [13] and pomegranates [14]. In a study to reduce the modulus of tomato elasticity, it was concluded that during transportation, the young modulus of the fruit decreases significantly [15].…”
Section: Introductionmentioning
confidence: 99%
“…The final two measures serve as indicators of bruising severity and often require exposure of fruit to higher impact energies to demonstrate the presence of a visible bruise. Bruise susceptibility information has recently been used to develop bruising thresholds, in terms of peak acceleration velocity (measured with an Instrumented Sphere) for peaches (Schulte et al 1994), using bruise occurrence as an indicator of susceptibility and for apples (Pang et al 1994) and peaches (Lin and Brusewitz 1994) using bruising severity as an indicator of susceptibility.…”
Section: Introductionmentioning
confidence: 99%